Electrospun silk for biomedical applications - Dai, Shufen; Liang, Huarun; Zhu, Mengjia; Zhang, Yingying (Med-X, 2024)
Electrospinning technology, capable of creating nanofiber-based materials with large specific surface areas and exceptional breathability, has become an important tool in the biomedical field. Silk, as a well-known natural biopolymer, features good biocompatibility, customizable biodegradability, and superior mechanical properties. The conversion of silk into nanofibers via electrospinning allows for the fine-tuning of its properties, thereby enhancing its suitability for a variety of biomedical applications. Electrospun silk not only inherits the natural advantages of silk but also acquires optimized characteristics such as increased surface area, high porosity, and good air permeability. This review article begins by summarizing the latest advances in the rational design and controlled fabrication of electrospun silk. Then, the biomedical applications of electrospun silk in three main areas: health monitoring, regenerative medicine, and personal protection, are reviewed. Lastly, the existing challenges and future perspectives of electrospun silk are discussed. This review aims to highlight the cutting-edge role of electrospun silk in biomedical applications, potentially revolutionizing traditional healthcare into a personalized model. Graphical Abstract Highlights • Rational design, controlled fabrication, and advantages of electrospun silk are discussed. • Biomedical applications, including health monitoring, regenerative medicine, and personal protection are systematically summarized. • Electrospun silk paves a compelling road to biomedical applications for personalized healthcare.